(untitled) (International Journal of Engineering and Computer Science, 2017)
In today’s scenario there are so many good websites which are powered by easy to use web content management systems (WCMS) that allow making changes to a website without needing to touch a single line of code. Now a days there is a substantial number of open source WCMS that are available as free for website developer. This research paper aims to make a comparison between three most commonly used WCMS (WordPress, Drupal and Joomla) that are present in the web world today. This comparison will guide which CMS should be selected based on their setup, plug-in, themes, multilingual-ness, security, scalability, administration, Role Management, flexibility, installation time and ease of customization.